Demographic Dividends, Gender Equality, and Economic Growth : The Case of Cabo Verde - Marone, Heloisa (IMF Working Papers; Working Paper, 2016)
This study analyzes Cabo Verde's demographic transition from the perspective of gender equality. As the pace of the demographic transition slows, promoting gender equality and increasing women's labor force participation will be progressively more important in enhancing otherwise slow-growth dynamics, reducing poverty, and improving the lives of all, women and men. The study investigates gender gaps in the labor market participation rate, employment conditions, and the use of time dedicated to unpaid work. It also discusses policy options to decrease the time women spend on unpaid work, enhance their employability, and enable them to secure employment. Overall, this study contributes to the debate on how better to manage the potential dividends resulting from demographic transitions on the still young but rapidly aging African continent.